the Influence of perceived leadership styles on burnout among nurses: the influence of perceived leadership styles on burnout among nurses - نعمة, اسراء (Karbala Journal of Medicine, 2024)
The study examines the relationship between nurses' job burnout and leadership styles in Karbala city teaching hospitals. The research was conducted in Iraq, in the city of Karbala, and included 324 nurses to explore how leadership styles and demographic factors affect job burnout. The results reveal a relationship between leadership style and reduced burnout among nurses, suggesting that effective leadership can positively impact nurses' well-being. Most of the participants were young people, and females constituted a large proportion of the sample. This study emphasizes the importance of leadership in alleviating nurse burnout and improving overall job satisfaction.